Exclusionary abuses of the dominant position by the energy companies in the EU through long-term natural gas supply contracts: application of Article 102 of the TFEU - Gesins, Aleksandrs (Riga Graduate School of Law, 2023)
The current thesis examines the scope of application of the Article 102 of the TFEU on the subject of exclusionary abuses of the dominant position by the energy companies in the European Union, stemming from the long-term natural gas supply contracts. The thesis provides a comprehensive research on the examination of the European Union natural gas market, competition law framework of the Article 102 of the TFEU, and its application to the specific contractual practices, which resulted in exclusionary abuses of the dominant position. Additionally, the thesis strives to identify economic implications of abusive exclusionary practices, which stem from the long-term natural gas supply contracts. Research focuses on the legal methodology through applying the scope of application of the Article 102 of the TFEU, soft law concepts developed by the European Commission, such as effects-based approach, and anti-competitive foreclosure approach on the practical examples of the contractual provisions of the long-term natural gas contracts. The thesis contributes to a better understanding of the role of Article 102 of the TFEU in promoting competitive markets in the natural gas industry, hence it highlights the capacity, applicability and effectiveness of the legal framework to regulate natural gas market competition, which could be subject to the abuse of dominance, therefore, creating negative effects on the economic development in the European Union.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::Competition law; Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; Exclusionary abuse of dominant position; Undertakings